PENGARUH TARI KREASI KOLABORASI TERHADAP PERKEMBANGAN METORIK KASAR ANAK USIA DINI DI TK MUSLIMAT CURAHLELE JEMBER - Umil Hosna; Ahmad Jazuly; Tohedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Collaborative Creative Dance on the gross motor development of early childhood students at TK Muslimat Curah Lele Jember. The research used a quantitative approach with a one-group pretest-posttest design. The research subjects were 10 children aged 5–6 years. The paired sample t-test analysis showed a significance value of 0.000 (< 0.05), indicating a significant effect. The N-Gain Score result was 0.53, indicating a moderate level of effectiveness. These findings suggest that Collaborative Creative Dance is an enjoyable and effective method for improving gross motor skills in early childhood education.